2021
DOI: 10.1186/s12884-021-03839-w
|View full text |Cite
|
Sign up to set email alerts
|

Pro-poor policies and improvements in maternal health outcomes in India

Abstract: Background Since 2005, India has experienced an impressive 77% reduction in maternal mortality compared to the global average of 43%. What explains this impressive performance in terms of reduction in maternal mortality and improvement in maternal health outcomes? This paper evaluates the effect of household wealth status on maternal mortality in India, and also separates out the performance of the Empowered Action Group (EAG) states and the Southern states of India. The results are discussed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…Government has always adopted an incentives based strategy to reduce or increase a maternal and child health care indicators. It was found that for reduction of maternal deaths demand side financing like conditional cash transfers have a played an important role [33]. Also, for increasing the acceptance of contraception uptake, well designed service delivery strategies are effective [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Government has always adopted an incentives based strategy to reduce or increase a maternal and child health care indicators. It was found that for reduction of maternal deaths demand side financing like conditional cash transfers have a played an important role [33]. Also, for increasing the acceptance of contraception uptake, well designed service delivery strategies are effective [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Between 1990 and 2018, the maternal mortality ratio in India decreased from 556 to 113 deaths per 100 000 live births ( Khetrapal, 2018 ; Office of the Registrar General India, 2020 ). The groundbreaking progress observed over the years (see Figure 1 ) was possible due to strong political commitment and implementation of multi-pronged initiatives under the National Health Mission ( Bhatia et al. , 2021 ) and the Department of Women and Child Development.…”
Section: Introductionmentioning
confidence: 99%
“…India struggles with significant MCH concerns, accounting about one quarter of the global burden of maternal and childhood mortality. 1 Low health literacy, socio-cultural norms, different living environment, poverty and inadequate local participation in decision making etc. are few of the identified reasons for several MCH related unmet needs among tribal people in India.…”
Section: Introductionmentioning
confidence: 99%